Socioeconomic Status and Child Health Conditions - Khimanand Pandey, Jyoti (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of the study is to find the association between child socioeconomic background (SEB) and health conditions of children of south Mumbai of Maharashtra. Methodology: A hospital cross-sectional research design was used by selecting 40 children from selected hospitals of south Mumbai using probability simple random technique. Data were collected with the help of structured interviews, structured questionnaires, and rating scale. Data get analyzed using descriptive and inferential statistics. Results: For parameter, “body mass index (BMI),” the beta value is (0.03), it means when we increase value of independent variable (child SEB) by 1, the value of dependent variable (BMI) will increase by 0.03, and there is very poor positive relation among BMI and composite score of socioeconomic background parameters. For parameter, “behavioral difficulty,” the beta value is −0.42, it means when we increase independent variable (child SEB) by 1, the value of dependent variable (behavioral difficulty) will decrease by 0.42. It indicated that there is inverse relation among behavioral difficulties and composite score of socioeconomic background parameters. For parameter, “sleep problem,” the beta value is (−0.67), it means when we increase independent variable (child SEB) on X axis by 1, the value of dependent variable (sleep problem) on Y axis will decrease by 0.67 and that’s why there is an inverse relationship among composite score of socioeconomic background parameters and sleep problems. Conclusion: Study has shown that there is a strong positive relation between child socioeconomic status and health condition of children.